THE IMPLEMENTATION OF SHARIA COMPLIANCE AUDITS IN IMPROVING CORPORATE INTEGRITY AND PERFORMANCE - Izzul Ashlah; Amin Zaki; Faisal Razak (Sharia Oikonomia Law Journal, 2026)
Increasing demands for transparency, accountability, and ethical governance have intensified the need for effective audit mechanisms within Sharia-compliant organizations. Sharia compliance audits have emerged as an important governance instrument designed to ensure that organizational activities, financial transactions, and operational practices adhere to Islamic principles while supporting sustainable organizational performance. Growing expansion of Islamic financial institutions and Sharia-oriented enterprises has heightened interest in understanding the broader impact of Sharia auditing beyond regulatory compliance. This study aims to examine the implementation of Sharia compliance audits and evaluate their effectiveness in improving corporate integrity and organizational performance. A quantitative research design was employed involving 350 managers, internal auditors, compliance officers, Sharia supervisory board members, and senior administrators from various Sharia-compliant institutions. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling (SEM). Findings indicate that Sharia compliance audit implementation significantly enhances corporate integrity by strengthening transparency, accountability, ethical conduct, and stakeholder trust. Results further reveal that effective audit implementation positively influences organizational performance, including operational efficiency, institutional sustainability, and stakeholder confidence. Corporate integrity was found to partially mediate the relationship between audit implementation and organizational performance, highlighting its strategic role in governance effectiveness. The study concludes that Sharia compliance audits function as comprehensive governance mechanisms that contribute not only to regulatory adherence but also to integrity enhancement and sustainable organizational performance within Sharia-oriented institutions.